(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2024)
Education on legality and citizenship rights is a central theme for all Italian universities that intersects with the broad debate that has recently concerned the definition of the “third mission” in our universities. The project “Roma Tre against the mafia”, sponsored by Libera and which includes in its first phase the naming of 12 departmental classrooms after innocent victims of the mafia, intends to be a contribution in this direction. Within this project, six classrooms have been dedicated to six women innocent victims of mafia violence, in the awareness that the criminal laws of mafia violence and those of patriarchy present a contiguity in the processes of oppression, annihilation and discrimination of women that must be further investigated. In fact, in mafia violence, women’s bodies become the object in some circumstances of unprecedented ferocity.